2014
DOI: 10.14260/jemds/2014/2457
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Big Five Personality Traits and Academic Performance in Medical Students

Abstract: It is often argued that a blend of personality characteristics is necessary for people to be successful in their career. Educators, researchers, and psychologists have been constantly searching for parsimonious set of variables that predicts patterns of students' behaviours and their relationship to academic achievement .so this study was done to find out the relationship between Big Five personality traits and academic achievement in an undergraduate medical students (n=150) .In this study All personality tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
1
4
0
1
Order By: Relevance
“…Also, the results indicated that agreeableness had a positive correlation with students' performance. This result is in line with that of previous studies (45). These students with such characteristics trust others and have a great sense of cooperation.…”
supporting
confidence: 92%
“…Also, the results indicated that agreeableness had a positive correlation with students' performance. This result is in line with that of previous studies (45). These students with such characteristics trust others and have a great sense of cooperation.…”
supporting
confidence: 92%
“…On the other hand, Meyer, Fleckenstein, Retelsdorf, and Köller (2019) stated that conscientiousness could predict the results of mathematics test scores and English achievement scores are significantly predicted by the openness to experience. However, previous studies such as Paunonen, and Ashton (2001);Furnham, Chamorro-Premuzic, and McDougall (2003); Duff, Boyle, Dunleavy, and Ferguson (2004); O'Connor and Paunonen (2007); Wang, Wang, and Dai (2011); Komarraju, Karau, Schmeck, and Avdic (2011);Hakimi, Hejazi, and Lavasani (2011); Beaujean, Firmin, Attai, Johnson, Firmin, and Mena (2011); Zupančič and Kavčič (2011);Lim, and Melissa Ng Abdullah (2012); Lee and Chae (2013); Nighute and Sadawarte (2014); Köseoğlu (2016); Novikova and Vorobyeva (2017); Varadwaj (2017); Kirkagac and Öz (2017); Raza and Shah (2017); Demetriou, Kazi, Spanoudis, and Makris (2019); Morales-Vives, Camps, and Dueñas (2020) found empirical evidence that among the five Big Five Personality, the most significant predictor of academic achievement is conscientiousness.…”
Section: Discussionmentioning
confidence: 98%
“…This study is in accordance with Ghazi, Shahzada, and Ullah (2013) which stated that the agreeableness personality type is related to the achievements of Islamic studies, including Arabic. Even though, Komarraju, Karau, Schmeck, and Avdic (2011); Nighute and Sadawarte (2014); Köseoğlu (2016); Kirkagac and Öz (2017); Varadwaj (2017) found that agreeableness is a significant predictor of academic achievement.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, Smrtnik- Vitulić & Zupančič (2011) revealed that students who have low extraversion personality types do not influence academic achievement. Similarly, Nighute, S., & Sadawarte, S. K. (2014) showed that the personality type of extraversion was not a significant predictor for academic achievement.…”
Section: Discussionmentioning
confidence: 99%